Acute leukaemia with a pure erythroid phenotype: under‐recognized morphological and cytogenetic signatures associated universally with primary refractory disease and a dismal clinical outcome. Issue 2 (5th May 2017) - Park, David C; Ozkaya, Neval; Lovitch, Scott B
Abstract : Aims: Pure erythroid leukaemia (PEL) is an extremely rare and aggressive subtype of acute myeloid leukaemia defined by the World Health Organization (WHO) as a neoplastic proliferation of immature cells committed exclusively to the erythroid lineage, comprising >80% of bone marrow cells and not meeting the criteria of other well‐defined myeloid neoplasms. The aim of this study was to describe the clinicopathological features of acute leukaemias with a pure erythroid phenotype (ALPEP) irrespective of their WHO classification and to determine if ALPEP represents a distinct clinicopathological entity. Methods and results: We identified seven cases of ALPEP, in which immature cells fulfilled WHO morphological and immunophenotypical criteria for PEL. All patients except one were male, with a median age of 60 years. Three cases represented de novo PEL, three were therapy‐related myeloid neoplasms and one was a blast phase of a myeloproliferative neoplasm. Extensive tumour necrosis was present in five cases (71%). Five cases with available modal karyotypes all demonstrated a complex karyotype involving the TP53 gene locus, with three cases (60%) also showing a monosomy 5 or deletion 5q and additional material on chromosome 19q13. All patients died of their disease, with a mean overall survival of 189 and 64.7 days in cases without and with necrosis on the initial biopsy, respectively. Conclusions: We describe previously unreported but relatively common findings of extensive tumour necrosis and recurring cytogenetic abnormalities in ALPEP. Our findings suggest strongly that ALPEP represents a distinct clinicopathological entity regardless of its WHO classification.